Role of Ionizable Lipids in SARS-CoV-2 Vaccines As Revealed by Molecular Dynamics Simulations: From Membrane Structure to Interaction with mRNA Fragments - Paloncýová, Markéta; Čechová, Petra; Šrejber, Martin; Kührová, Petra; Otyepka, Michal (The journal of physical chemistry letters, 2021)
Recent advances in RNA-based medicine have provided new opportunities for the global current challenge, i.e., the COVID-19 pandemic. Novel vaccines are based on a messenger RNA (mRNA) motif with a lipid nanoparticle (LNP) vector, consisting of high content of unique pH-sensitive ionizable lipids (ILs). Here we provide molecular insights into the role of the ILs and lipid mixtures used in current mRNA vaccines. We observed that the lipid mixtures adopted a nonlamellar organization, with ILs separating into a very disordered, pH-sensitive phase. We describe structural differences of the two ILs leading to their different congregation, with implications for the vaccine stability. Finally, as RNA interacts preferentially with IL-rich phases located at the regions with high curvature of lipid phase, local changes in RNA flexibility and base pairing are induced by lipids. A proper atomistic understanding of RNA-lipid interactions may enable rational tailoring of LNP composition for efficient RNA delivery.
Keywords: Lipids; Models, Molecular; simulace molekulární dynamiky; Lipid Bilayers; RNA, Messenger; lipidové dvojvrstvy; lipidy; Humans; vakcíny proti COVID-19; messenger RNA; lidé; Molecular Dynamics Simulation; molekulární modely; COVID-19 Vaccines